PERBANDINGAN METODE CERAMAH DAN VIDEO INTERAKTIF UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA PADA MATERI FLUIDA - Rodiah, Isyatun; Basril, Basril (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
This study aims to compare the effectiveness of the lecture method and interactive video learning in improving students’ critical thinking skills on fluid mechanics material. The research used a quasi-experimental design involving two classes: one taught through conventional lectures and the other using YouTube-based interactive videos. Both groups were given pretests and posttests, and the improvement in critical thinking skills was analyzed using the N-Gain formula. The findings show that both learning methods resulted in an increase, with the lecture class achieving a slightly higher and more evenly distributed N-Gain score. The interactive video class also showed significant improvement, although the variation among students was wider, indicating differences in digital literacy and learning focus. These results suggest that while lectures remain effective for building structured understanding, interactive videos provide strong visual support that promotes analytical thinking. The combination of both methods may offer a more optimal approach for developing students’ critical thinking skills. This study highlights the importance of selecting learning strategies that accommodate diverse learning styles and the need for continued integration of technology in physics education.